Influence of cholecystectomy on sphincter of Oddi motility. Issue 3 (1st September 1997) - Luman, W; Williams, A J K; Pryde, A; Smith, G D; Nixon, S J; Heading, R C; Palmer, K R
Abstract : Background —Gall bladder and sphincter of Oddi (SO) function are coordinated by hormonal and neuronal mechanisms. Nerve fibres pass between the gall bladder and the SO via the cystic duct. It is therefore possible that cholecystectomy may alter SO motility. Aim —To investigate the effect of cholecystectomy on SO function Methods —SO manometry was performed in five women (median age 52 years), a few days before and six months after laparoscopic cholecystectomy which was undertaken for uncomplicated cholelithiasis. Basal and post-cholecystokinin (CCK) SO motility were measured. Results —All patients were symptom free after laparoscopic cholecystectomy. Prior to surgery common bile duct pressure, and tonic and phasic SO motility were normal and phasic contractions were inhibited by intravenous CCK (1 Ivy Dog Unit/kg). Six months later, common bile duct pressure and baseline tonic and phasic activity were unchanged but CCK failed to suppress phasic activity. Conclusion —Cholecystectomy, at least in the short term, suppresses the normal inhibitory effect of pharmacological doses of CCK on the SO. The mechanism of this effect is unknown but it could be due to SO denervation.